Analyzing Students' Problems in Pronunciation During Their Self-Study in Pandemic Situation - Jacob, Elizenda (Huele: Journal of Applied Linguistics, Literature and Culture, 2022)
This study investigates the pronunciation practices of English Department students during self-study amid the COVID-19 pandemic. With the shift to online learning, students increasingly engaged in self-directed learning activities to enhance their pronunciation skills. A survey was conducted with 70 students to explore their preferred pronunciation activities, the challenges they faced, and the strategies employed to overcome these challenges. The findings reveal that students favored listening to English songs and watching movies as primary methods for practicing pronunciation. However, they encountered significant difficulties, such as distinguishing similar-sounding vocabulary and limited opportunities for speaking practice. To address these issues, students utilized various strategies, including online resources, peer collaboration, and self-recording. This research highlights the critical role of self-study in language acquisition and emphasizes the importance of pronunciation as a key component of effective communication. The study underscores the need for educators to incorporate engaging resources and structured feedback to support students in their pronunciation development.